Conocimientos y actitudes sobre anticoncepción oral de emergencia en adolescentes de la comunidad de San Francisco-Río Itaya Belén 2022 - Shapiama Freitas, Juan Sergio (2025)
The formulation of the study problem was, What is the relationship that exists between knowledge and attitudes about emergency oral contraception in adolescents from the community of San Francisco - Río Itaya, Belén 2022? The objective was to determine the relationship that exists between knowledge and attitudes about emergency oral contraception in adolescents from the community of San Francisco-Río Itaya, Belén 2022. The study was quantitative, descriptive, correlational, cross-sectional and prospective, with a sample of 180 adolescents, the instrument used was the questionnaire, validated by expert judgment, reaching 93% validity, for statistical analysis Chi square was used.from Spanish. The study found in the sociodemographic characteristics: adolescents from 12 to 14 years old (56.1%), male (55.6%), secondary education level (66.1%), student occupation (95.6%) and single marital status (86.1%). The level of knowledge about the use of emergency oral contraceptives was low (90.6%) and the attitude was low (92.8%). It is concluded that there is no direct relationship between the variable knowledge and attitude, p>0.05.